2018
DOI: 10.1136/bmjopen-2017-020625
|View full text |Cite
|
Sign up to set email alerts
|

Should surgery be delayed in patients taking direct oral anticoagulants who suffer a hip fracture? A retrospective, case-controlled observational study at a UK major trauma centre

Abstract: ObjectiveTo determine whether not waiting for the elimination of direct oral anticoagulants (DOACs) has an effect on the amount of perioperative bleeding in patients who undergo operative treatment of a hip fracture.DesignObservation, retrospective case–control study.SettingA single UK major trauma centre.ParticipantsPatients who sustained a hip fracture were identified using the National Hip Fracture Database (NHFD). All those found to be taking a DOAC at the time of fracture were identified (n=63). A matched… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
62
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(65 citation statements)
references
References 38 publications
3
62
0
Order By: Relevance
“…In contrast, our DOAC-using patients did not wait significantly longer for surgery than the non-users. Another study investigated hip fracture patients using DOACs compared to matched controls with a median of only 19 h from admission to surgery [30]; no association between surgical delay and perioperative fall in haemoglobin, transfusion rate or reoperation for DOAC-users was found. As our study did not find increased bleeding-and transfusion-complications among patients using DOAC, early surgical interventions appear safe.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, our DOAC-using patients did not wait significantly longer for surgery than the non-users. Another study investigated hip fracture patients using DOACs compared to matched controls with a median of only 19 h from admission to surgery [30]; no association between surgical delay and perioperative fall in haemoglobin, transfusion rate or reoperation for DOAC-users was found. As our study did not find increased bleeding-and transfusion-complications among patients using DOAC, early surgical interventions appear safe.…”
Section: Discussionmentioning
confidence: 99%
“…We need to acknowledge that reoperation due to wound ooze is a late solution to persisting oozing. One earlier study has investigated DOAC-users' risk of reoperation due to wound ooze and found no relation to surgical delay [30]. On the other hand, when studying hip fracture patients not accounting for chronic anticoagulation, surgical delay has been found to be a risk factor for wound infections [28,33].…”
Section: Discussionmentioning
confidence: 99%
“…Its cost has restricted its widespread use. A recent study using audit data from a single hospital reported that hip fracture surgery for patients taking DOAC had a median time to theatre of 19 h [22]. Compared to a matched cohort, there was no difference in perioperative haemoglobin concentration, requirement for transfusion and reoperation suggesting that early surgery is possible even for patients on DOACs [22].…”
Section: Discussionmentioning
confidence: 99%
“…A recent study using audit data from a single hospital reported that hip fracture surgery for patients taking DOAC had a median time to theatre of 19 h [22]. Compared to a matched cohort, there was no difference in perioperative haemoglobin concentration, requirement for transfusion and reoperation suggesting that early surgery is possible even for patients on DOACs [22]. Our own study reported a median time to theatre of 27 h, which is within the required 36 h to achieve UK Best Practice Tariff for hip fracture management, a payment tariff for hospitals set nationally.…”
Section: Discussionmentioning
confidence: 99%
“…All these drugs will increase risk of perioperative bleeding at the fracture site, but an even greater concern is bleeding related to spinal anesthesia which can cause spinal injury. A recent study showed that perioperative bleeding and 30days mortality were not increased by use of DOAC without delay in surgery [43]. However, it is recommended to stop DOACs at admission and wait for 24-48 hours after last dose has been taken before spinal anesthesia can be given.…”
Section: A Antithrombotic Treatmentmentioning
confidence: 99%